SOCIAL MEDIA MARKETING STRATEGY IN INCREASING BRAND AWARENESS - Wilis, Ratih Anggoro (LPPM STIE Muhammadiah Bandung, 2023)
This study aims to analyze the engagement of the Instagram account @mamitoko and @mamitoko_store which influence Brand Awareness, by observing 3 (three) elements in analyzing social media interaction, such as creator-related features, contextual features, and content features. This study uses a qualitative method with a descriptive approach by conducting interviews with users. The author used the Miles and Hubberman model and tested the validity of the data using the source transulation technique. The results of this study show that the Instagram account @mamitoko and @mamitoko_store have an admin who manages social media. Based on the author's analysis, the engagement of @mamitoko_store is not optimal. Soft-selling content is more attractive to visitors, besides that visitors are more interested in educative content, detailed information content, and interactive content.